2005
DOI: 10.1270/jsbbs.55.163
|View full text |Cite
|
Sign up to set email alerts
|

Putative UDP-galactose Epimerase and Metallothioneine of <i>Paspalum vaginatum</i> Enhanced the Salt Tolerance of Rice, <i>Oryza sativa</i> L. from Transplanting to Harvest Stages

Abstract: Defining seawater tolerance as a plant's ability to survive under saline culture (seawater: average 500 mM NaCl), we attempted to identify gene sources as donors for this trait. Seawater-tolerance was observed in 42 plant species and spread over many families. In the family Gramineae, the presence of seawater tolerance was not random: a large cluster of seawater tolerance was found in the sub-family Eragrostoideae. In contrast, most grass crops, belonging to different sub-families, were susceptible in seawater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…A number of genes have also been isolated and characterized from Porteresia coarctata that are related to the salt tolerance property of the plant, specially the genes operational in inositol metabolic pathway such as myoinositol phosphate synthase ( PcMIPS ) has been analysed in details (Sengupta and Majumder 2009 ). A putative UDP galactose epimerase gene and a metallothioneine gene was reported to play an important role in conferring salt tolerance to salt tolerant plants of Paspalum vaginatum (Endo et al 2005 ). Wang et al ( 2007 ) identified 162 unique transcripts corresponding to possible salt-related genes in P tenuiflora .…”
Section: Reviewmentioning
confidence: 99%
“…A number of genes have also been isolated and characterized from Porteresia coarctata that are related to the salt tolerance property of the plant, specially the genes operational in inositol metabolic pathway such as myoinositol phosphate synthase ( PcMIPS ) has been analysed in details (Sengupta and Majumder 2009 ). A putative UDP galactose epimerase gene and a metallothioneine gene was reported to play an important role in conferring salt tolerance to salt tolerant plants of Paspalum vaginatum (Endo et al 2005 ). Wang et al ( 2007 ) identified 162 unique transcripts corresponding to possible salt-related genes in P tenuiflora .…”
Section: Reviewmentioning
confidence: 99%
“…It has been reported that a drought resistance QTL in rice was identified as a putative UGE gene, and the cDNA clone was mapped within the root thickness QTL region on chromosome 7 showed significant similarity to OsUGE-1 (Nguyen et al, 2004). Recently, another study also reported increased salt tolerance in rice by over-expressing a putative UGE, which was designated as PvUGE1 (Endo et al, 2005). Although UGE family has been indicated to function in abiotic stress, up to date, few studies have investigated the mechanism of their role responding to abiotic stress.…”
Section: Article In Pressmentioning
confidence: 99%
“…It is able to survive in a wide variety of habitats and conditions, including submergence, saline environments, and drought (Frasier and Johnsen 1991). Tamarix appears to grow best in saline soils and can tolerate solutions with higher salt levels than that of seawater (Endo et al 2005). The genus Tamarix is native to a zone that stretches from southern Europe and North Africa through the Middle East and south Asia to China (Frasier and Johnsen 1991).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Rice was transformed as described elsewhere (Endo et al 2005). Regenerated plantlets (T 0 generation) were transferred into a confined greenhouse and grown until flowering in soil-containing pots.…”
Section: Transformation In Ricementioning
confidence: 99%